Morphology of the Arabic language in the book of al-HusamuddinSygnaki "An-Nazhah al-TalitiluaMarah" - Kurmanbayev К (Journal of Oriental Studies, 2016)
This article considers the book "Kitab Al-Nazhah fi al-Ilmi sarf" related to Arabic linguistics known theologian and legal scholar of Kazakh steppes of the XIII century Husamuddin al-Sygnaki